Branded lives : the production and consumption of meaning at work - Brannan, Matthew J.; Parsons, Elizabeth; Priola, Vincenza, 1970- (Cheltenham, UK : Edward Elgar Publishing, 2011)
'Branded Lives explores the increasingly popular concept of employee branding as a new form of employment relationship based on brand representation. In doing so it examines the ways in which the production and consumption of meaning at work are increasingly mediated by the brand. This insightful collection draws on qualitative empirical studies in a range of contexts to include services, retail and manufacturing organizations'--P. 4 of cover.
Includes bibliographical references and index.
Also available in digital form.
Keywords: Branding (Marketing); Product management; Quality of work life; Industrial relations; Personnel management